The election of grace : a riddle without a resolution? - Williams, Stephen N. (Stephen Nantlais) (Grand Rapids, MI, William B Eerdmans Publishing Company, 2015)
Few issues in Christian theology have sparked as much controversy over the centuries as the question of election ... After expounding the Bible's teaching on election, Williams turns to questions of theological method and substance. He maintains that the subject of predestination must be considered in a wider biblical context than it often is and that we cannot expect to understand election within a comprehensive systematic framework. What matters is the relation of particular truths to the particulars of life, he says, not the systematic relation of truths to each other. Williams draws on and applies the insights of remarkable nineteenth-century Anglican leader Charles Simeon throughout his study, concluding the book with a cogent discussion of Karl Barth on election.--Provided by publisher
Election in the Old Testament -- New Testament election -- Dogmatic limits -- Dogmatic difficulties -- Appendix: Karl Barth on election.
Includes bibliographical references and index.
Includes bibliographical references and index.
Keywords: Election (Theology)